Cyclic behavior of connections equipped with NiTi shape memory alloy and steel tendons between H-shaped beam to CHS column. (1st April 2015) - Wang, Wei; Chan, Tak-Ming; Shao, Hongliang; Chen, Yiyi
Highlights: A novel connection integrating with superelastic SMA tendons and steel tendons is proposed. Six full-scale H-beam-to-CHS-column connections were tested under cyclic loads. Connections demonstrated excellent recentering capability and moderate energy dissipation. Tendons' length and configuration are crucial design parameters. Abstract: Shape memory alloys (SMAs) are a class of smart materials which are able to undergo large deformations while reverting back to their original undeformed shape upon heating or by relieving the stress that causes the deformation. When they are equipped in connections within a structural steel frame, this unique property could enhance the recentering capability of the structure after severe event. In this paper, a novel connection – integrating superelastic SMA tendons with steel tendons, is proposed between a H-shaped beam to a CHS column. Six full-scale prototype specimens with different combination of SMA and steel tendons were tested to evaluate the recentering capability and the energy dissipative performance. The novel connection consists of SMA tendons with original diameter of 12 mm, steel tendons with original diameter of 12 mm, extended end-plate, external diaphragm and beam flange ribs. Test results showed that connections equipped with SMA tendons exhibit moderate energy dissipation, double-flag-shaped hysteresis loops and excellent recentering capability after being subjected to cyclic loads up to 6% interstory drift angle.